Candida auris Infection Among Patients With Cancer in an Oncology Center in Eastern India. (October 2020) - Bhattacharya, Sanjay; Das, Parijat; Goel, Gaurav; Mukherjee, Sudipta; Ghosh, Pralay Shankar; Singh, Rohit; Sinha, Subir; Chandy, Mammen; Walia, Kamini; Chakrabarti, Arunaloke
Abstract : Background: The multidrug-resistant fungus Candida auris is emerging as a major cause of healthcare-associated infection globally. Understanding the epidemiology of these infections in vulnerable groups such as cancer patients is important for hospital infection control and their effective management. In this report we present diagnostic, clinical, antifungal resistance and outcome data of 11 cases of C. auris infection from an oncology center in India. Methods: C. auris strains were identified by Sanger-based DNA sequencing of the internal transcriber spacer (ITS) gene. Antifungal susceptibility testing (AFST) was performed using the broth dilution method. Identification and AFST were checked by the WHO Collaborating Center for Reference & Research on Fungi of Medical Importance. Patients had both empirical as well as directed therapy with antifungal agents based on AFST results and clinical assessment. Results: Between November 2018 and March 2019, 11 cases of C. auris (8 from patients with solid-organ tumors and 3 from hematological malignancy) were detected. Two distinct genetic clusters were identified by ITS gene sequencing; one of these clusters showed 100% homology with a previously unknown C. auris isolate (GenBank accession no. MK881076) and the other cluster had a 100% identity score with isolates from Japan and South Korea (GenBank accession nos. MH071441, KY657027, and EU884189). All 11 strains were resistant to fluconazole. With voriconazole, 1 isolate was susceptible, 3 were resistant, and 7 showed dose-dependent susceptibility. Two isolates were resistant to amphotericin B. Resistance to caspofungin or anidulafungin was noted in 1 of 11 isolates (9%); most showed intermediate susceptibility (63% to caspofungin). Among all of the patients, 72% were from the intensive care unit (ICU) or the high-dependency unit. The 30-day all-cause mortality was 5 of 11 (45%) in the C. auris group and 4 of 11 (36%) the control group (ie, infections with other Candida spp during same period). Duration of ICU stay in the C. auris group was 12 days and in the control group it was 6 days. The median cost (in terms of hospital bill at the time of discharge or death) for management of Candida auris infection and the primary medical condition was US$10, 121 for the C. auris groups and US$8, 608 for the control group. Most cases (10 of 11) were detected in wards without isolation rooms, and 8 of the 11 C. auris cases (73%) were detected in patients in the intensive care unit. Conclusions: Morbidity, mortality, ICU stay, and healthcare costs are significant in C. auris infection. Funding: None Disclosures: None